2019
DOI: 10.1097/md.0000000000015372
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of limited-incision versus standard-incision in treatment of carpal tunnel syndrome

Abstract: Background: Carpal tunnel syndrome is a common compressive neuropathy of the median nerve. Compared with standard release, the efficacy, safety, and postoperative complications of limited carpal tunnel release remain controversial. The purpose of this study was to compare the effects of the 2 treatments. Methods: The English-language literature was searched using MEDLINE, Web of Science, and Embase. Randomized controlled trials that compared standard and limited incisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…This randomized controlled trial demonstrated that there were no differences in terms of early postoperative anterior wrist pain or time to return to work or to activities of daily living between the MIS with tool-kit and the short incision patients who underwent CTS release. Our results differ significantly from a recent meta-analysis [ 15 ]. Among the reasons for the difference might be the relatively small difference in wound length between the MIS with tool-kit and the short incision groups (1.95 (SD 0.47) cm vs 2.92 (SD 0.56) cm) in this study which had small effect size.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This randomized controlled trial demonstrated that there were no differences in terms of early postoperative anterior wrist pain or time to return to work or to activities of daily living between the MIS with tool-kit and the short incision patients who underwent CTS release. Our results differ significantly from a recent meta-analysis [ 15 ]. Among the reasons for the difference might be the relatively small difference in wound length between the MIS with tool-kit and the short incision groups (1.95 (SD 0.47) cm vs 2.92 (SD 0.56) cm) in this study which had small effect size.…”
Section: Discussioncontrasting
confidence: 99%
“…Meta-analyses of previous publications have reported no significant difference in terms of symptom relief or functional improvement in the short- or long-term between open and endoscopic carpal tunnel release [ 11 – 13 ]. However, earlier return to work or activities of daily living and lower scar-related complications were found in smaller incision group with large difference of surgical wound length (open versus endoscopic carpal tunnel release or limited-incision versus standard-incision) [ 11 – 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high heterogeneity was mainly because of the fact that the data compared mini-incisions with endoscopic incisions. Miniincisions are not directly comparable to the standard incisions in OCTR, as they yield a better appearance and tend to have fewer wound-related complications than standard incisions [58].…”
Section: Discussionmentioning
confidence: 99%
“…The high heterogeneity was mainly because of the fact that the data compared mini-incisions with endoscopic incisions. Mini-incisions are not directly comparable to the standard incisions in OCTR, as they yield a better appearance and tend to have fewer wound-related complications than standard incisions [55].…”
Section: Discussionmentioning
confidence: 99%